Pelatihan Read Aloud untuk Meningkatkan Kemampuan Literasi Digital Guru di Kota Tangerang Selatan - Ika Tri Yunianika; Siti Hadianti; Refisa Ananda; Nunung Supratmi (Jurnal Pengabdian UNDIKMA, 2022)
This community service program aims to improve the digital literacy skills of teachers in Kota Tangerang Selatan through read aloud training. This program was carried out using training method based on needs analysis of primary teachers in Kota Tangerang Selatan. The read aloud training through digital library consisting of four stages, namely: preparation, implementation, monitoring, and evaluation. The training was conducted online through the Zoom platform. Participants of this program consist of 58 teachers from 12 primary schools in Kota Tangerang Selatan. The instrument of evaluation used in this program was Kirkpatrick’s training evaluation model (level 1). Questionnaires of evaluation were distributed through google form. The evaluation data were analyzed using descriptive analysis. The results of this training were the improvement of teachers’ knowledge regarding read aloud, the development of teachers’ skills to use read aloud technic properly for teaching, and the improvement of teachers’ ability to access digital library and to use it in teaching learning process.